Mass culture strategy for bacterial yeast co-culture for degradation of petroleum hydrocarbons in marine environment. Issue 1 (15th November 2015) - Priya, Anchal; Mandal, Ajoy K.; Ball, Andrew S.; Manefield, Mike; Lal, Banwari; Sarma, Priyangshu M.
Abstract: In the present study a metabolically versatile co-culture with two Bacilli and one yeast strain was developed using enrichment culture techniques. The developed co-culture had affinity to degrade both aliphatic and aromatic fractions of petroleum crude oil. Degradation kinetics was established for designing the fermentation protocol of the co-culture. The developed mass culture strategy led to achieve the reduction in surface tension (26 dynes cm − 1 from 69 dynes cm − 1 ) and degradation of 67% in bench scale experiments. The total crude oil degradation of 96% was achieved in 4000 l of natural seawater after 28 days without adding any nutrients. The survival of the augmented co-culture was maintained (10 9 cells ml − 1 ) in contaminated marine environment. The mass culture protocol devised for the bioaugmentation was a key breakthrough that was subsequently used for pilot scale studies with 100 l and 4000 l of natural seawater for potential application in marine oil spills. Highlights: Development of co-culture with two bacteria and a yeast strain Petroleum crude oil degradation in marine environment Degradation of model aliphatic and aromatic hydrocarbons Mass culture strategy for the developed co-culture in 150 l bioreactor Bioaugmentation: mesocosm 100 l (Bay of Bengal) and Pilot Scale 4000 l (Arabian Sea)